2009
DOI: 10.4314/ijbcs.v2i4.39762
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amodiaquine on some brain macromolecules of Wistar rats

Abstract: Amodiaquine (AQ) is a 4-aminoquinoline antimalarial with schizonticidal action against different strains of Plasmodia. This study assessed the effect of the drug on some macromolecules of the brain of albino Wistar rats. Twenty-four adult Wistar rats weighing between 150-180 g were divided into four groups of six animals each. Group 1 served as the control and received distilled water, while groups 2, 3 and 4, the experimental groups, were treated with 17.50 mg/kg, 8.75 mg/kg and 8.75 mg/kg of AQ, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Other studies also showed a significant reduction in total cholesterol in the brain of Wistar rats on AQ and a greater degree of lipid peroxidation in malaria infected mice on AS/AQ treatment . These changes were attributed to the alteration in enzymatic and nonenzymatic antioxidant defence systems which give rise to increased lipid peroxidation . The similar pattern of changes observed in the pregnant control with respect to reduction in serum transaminases and elevation in alkaline phosphatase level when compared with the nonpregnant control may just be physiological.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Other studies also showed a significant reduction in total cholesterol in the brain of Wistar rats on AQ and a greater degree of lipid peroxidation in malaria infected mice on AS/AQ treatment . These changes were attributed to the alteration in enzymatic and nonenzymatic antioxidant defence systems which give rise to increased lipid peroxidation . The similar pattern of changes observed in the pregnant control with respect to reduction in serum transaminases and elevation in alkaline phosphatase level when compared with the nonpregnant control may just be physiological.…”
Section: Discussionmentioning
confidence: 71%
“…also suggested a significantly increased lipid treatment peroxidation in pregnant and nonpregnant women with malaria who received treatment for malaria. Other studies also showed a significant reduction in total cholesterol in the brain of Wistar rats on AQ and a greater degree of lipid peroxidation in malaria infected mice on AS/AQ treatment . These changes were attributed to the alteration in enzymatic and nonenzymatic antioxidant defence systems which give rise to increased lipid peroxidation .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Artesunateamodiaquine combination was the least prescribed ACT and was recommended only in the private health facility. Howbeit, its use was very low and this may not be unrelated to factors such as adverse effects such as described by Ekong et al (2008) who reported effects of amodiaquine on the brain macromolecules of Wistar rats. ACTs became the mainstay of antimalarial therapy following global reports of resistance to previously used antimalarial drugs such as chloroquine and sulphadoxine-pyrimethamine.…”
Section: Discussionmentioning
confidence: 98%
“…Amodiaquine, along with related 4-aminoquinolines such as chloroquine and hydroxychloroquine, was originally developed for the treatment of malaria [42], and like chloroquine and hydroxychloroquine, possesses widespread anatomical volume of distribution, including eyes and brain [43][44][45][46][47][48][49]. Antiviral compound penetrance into the CNS and/or ocular compartments is particularly relevant in the case of FIPV-infected cats with neurologic and/or ocular involvement.…”
Section: Discussionmentioning
confidence: 99%